Zeolite-polyamide thin film nanocomposite membranes : towards enhanced performance for forward osmosis - Ma, Ning (2012)
Zeolite-polyamide thin film nanocomposite (TFN) membranes were prepared on a polysulfone (PSf) porous substrate tailored for forward osmosis (thin thickness, high porosity, and straight needle-like pores). The TFN membranes were characterized and evaluated in comparison with a thin film composite (TFC) membrane. The incorporation of NaY zeolite nanoparticles in the polyamide rejection layer significantly changed its separation properties. In the range of 0.02–0.1 wt./v% zeolite loading, the incorporation of zeolite-polyamide exhibited enhanced water permeability of membrane likely due to the porous nature of zeolite. However, further increase in zeolite loading led to a reduction in water permeability, possibly as a result of the formation of a thicker polyamide layer. The most permeable TFN membrane (TFN0.1, with 0.1 wt./v% zeolite loading) had a water permeability approximately 80% higher compared to the baseline TFC membrane. The FO water flux followed a similar trend to that of the membrane water permeability. Under all cases evaluated in the current study (0.5–2.0 NaCl draw solution, DI water and 10 mM NaCl feed solution, and both membrane orientations), the membrane TFN0.1 exhibited highest water flux (up to 50% improvement over the TFC membrane). To the best knowledge of the authors, this is the first report on zeolite-polyamide based TFN membranes for FO applications.